2019
DOI: 10.1016/j.ajoc.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

A complex choristoma presenting as a salmon patch lesion in the bulbar conjunctiva

Abstract: PurposeWe describe a rare case of a complex choristoma appearing as a salmon-patch lesion in the nasal conjunctiva. While benign, complex choristomas are grossly indistinguishable from malignant lesions, and an excisional biopsy is warranted to confirm the diagnosis.ObservationsA 31-year-old man presented with an elevated glistening pink mass on the conjunctiva. An excisional biopsy with a “no-touch” technique was performed, followed by placement of an amniotic membrane graft without postoperative complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…5 In contrast, Oh et al reported a case of complex cartilaginous choristoma presenting as a salmon-patch lesion in the nasal epibulbar area with superficial vascularization and no corneal involvement. 7 Our report features a epibulbar lesion with multiple pigmented cysts, which has not been reported previously in association with a cartilaginous choristoma. The cysts were not characteristic of those typically seen as part of a cystic nevus, as they were larger and more numerous.…”
Section: Np102supporting
confidence: 42%
See 1 more Smart Citation
“…5 In contrast, Oh et al reported a case of complex cartilaginous choristoma presenting as a salmon-patch lesion in the nasal epibulbar area with superficial vascularization and no corneal involvement. 7 Our report features a epibulbar lesion with multiple pigmented cysts, which has not been reported previously in association with a cartilaginous choristoma. The cysts were not characteristic of those typically seen as part of a cystic nevus, as they were larger and more numerous.…”
Section: Np102supporting
confidence: 42%
“…In most reported cases, the cartilage is part of a complex choristoma that also includes other components such as lacrimal gland tissue, nerves, and smooth muscle. 2,57 Such complex choristomas may be part of syndromes including the organoid nevus syndrome or the nevus sebaceous of Jadassohn. 2 Furthermore, while most lesions involve the epibulbar space, non-epibulbar regions such as the eyelid have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] While it can occur anywhere in the body, it is more frequently observed in the head and neck region, especially in the pituitary gland [ 2 ] and oral cavity. [ 3 ] Intraspinal choristomas are rare and, to the best of our knowledge, only 2 cases have been reported. [ 4 , 5 ] Thus, it is pretty rare for choristoma to occur in the spinal canal.…”
Section: Introductionmentioning
confidence: 99%